The Implementation of Youth Reproductive Health Services in During the Covid-19 Pandemic - Sri Hawari Jannati; Andari Wuri Astuti; Dwi Ernawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The Covid-19 pandemic has changed and has an impact on all aspects, including adolescent reproductive health services. Adolescents face a variety of reproductive health risks that, if not addressed properly, can have long-term consequences. This review aims to determine the implementation of adolescent reproductive health services during the Covid-19 pandemic. Scoping review employed databases such as PubMed, Proquest, Science Direct, and Wiley Online Library to adapt the Arksey and O'Malley frameworks. There were 8 articles out of 550 which were selected based on inclusion and exclusion criteria. The Mixed Method Appraisal Tool (MMAT)was used to evaluate the articles in this scoping review. The results of the review showed changes in reproductive health services during the COVID-19 pandemic. As for the obstacles experienced by adolescents in accessing reproductive health services before the pandemic, there were barriers that came from the individual itself, socio-culture and society, in this case it is necessary to carry out several strategies related to the provision of reproductive health services during the Covid-19 pandemic both in terms of technology and changes in government regulations. Abstrak: Pandemi Covid-19 telah mengubah dan berdampak pada segala aspek, salah satunya aspek pelayanan kesehatan reproduksi remaja. Usia remaja dihadapkan dengan berbagai macam risiko kesehatan reproduksi yang apabila tidak dikelola dengan baik akan mengakibatkan konsekuensi yang berkepanjangan. Review ini bertujuan untuk mengetahui implementasi pelayanan kesehatan reproduksi remaja selama masa pandemi Covid-19. Scoping review mengadaptasi framework Arksey dan O’Malley dengan menggunakan database yaitu PubMed, Proquest, Science Direct, dan Wiley Online Library. Didapatkan sebanyak 8 artikel dari 550 yang diseleksi berdasarkan kriteria inklusi dan eksklusi. Penilaian artikel dalam scoping review ini menggunakan Mixed Method Appraisal Tool (MMAT). Hasil review ditemukan terjadinya perubahan pelayanan kesehatan reproduksi dimasa pandemi covid-19. Adapun terkait dengan Hambatan yang dialami oleh remaja dalam mengakses layanan kesehatan reproduksi sebelum terjadinya pandemi yaitu hambatan yang berasal dari individu sendiri, sosial budaya dan masyarakat, maka dalam hal ini perlu dilakukan beberapa strategi terkait dengan pemberian pelayanan Kesehatan reproduksi selama masa pandemi Covid-19 baik dari segi teknologi dan perubahan peraturan pemerintah.